2018
DOI: 10.1016/j.jaci.2017.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IL-17–committed T cells in a murine psoriasis model by a vitamin D analogue

Abstract: Topical CAL can exert its antipsoriatic effect on CAL-treated lesions and, concomitantly, distant lesions by attenuating the T17 cell accumulation in both CAL-treated lesions and draining lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 80 publications
5
33
0
Order By: Relevance
“…Although recent developments and success in the use of biologic therapies highlighted that immune regulation plays a vital role in the development of psoriasis, there is also cumulative evidence that www.nature.com/scientificreports www.nature.com/scientificreports/ interaction of epidermal factors and the immune system play a synergistic role in the initiation and maintenance of disease. Since clinical studies have practical and ethical limitations, conventional 2D culture and animal models have been widely utilized [41][42][43][44][45][46][47] . A large body of previous research focused on developing 3D in vitro psoriasis models, which can mimic psoriasis pathophysiology [14][15][16][17][18][19]48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…Although recent developments and success in the use of biologic therapies highlighted that immune regulation plays a vital role in the development of psoriasis, there is also cumulative evidence that www.nature.com/scientificreports www.nature.com/scientificreports/ interaction of epidermal factors and the immune system play a synergistic role in the initiation and maintenance of disease. Since clinical studies have practical and ethical limitations, conventional 2D culture and animal models have been widely utilized [41][42][43][44][45][46][47] . A large body of previous research focused on developing 3D in vitro psoriasis models, which can mimic psoriasis pathophysiology [14][15][16][17][18][19]48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was shown that Cal acted on DCs and T cells in ex vivo-cultured human psoriatic skin explants to inhibit IL-23 and IL-17 expression, respectively (26). More recently, it was reported that Cal suppressed the IL-23 expression by epidermal LCs, which was assumed to be the reason for the inhibition of IL-17 by Cal in Ald-induced mouse psoriasis (27). In our study, we showed that the inhibition of IL-23/IL-17/IL-22 by Cal was abolished in Vdr KC-/-(mice with the ablation of VDR selectively in KCs) ( Figure 2, A and B), which demonstrates that this inhibiting effect is actually dependent on keratinocytic VDR.…”
Section: Discussionmentioning
confidence: 99%
“…This has led us to uncover a mechanism showing that Cal acts on KCs instead of immune cells (such as T cells, DCs, or Langerhans cells [LCs]; refs. 26,27) to suppress the IL-23/IL-17 inflammatory axis in psoriasis and, furthermore, to provide evidence about how the combination of Cal and dexamethasone (Dex) effectively disrupt the positive cytokine feedback loop of IL-36 and IL-23/IL-17, which we believe underlies the superior efficacy of the combination therapy for psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…The so‐called biologics that target TNFα (etanercept, infliximab, adalimumab), IL12/23 (ustekinumab) and IL‐17 (secukinumab, ixikizumab) and small molecules targeting the downstream JAK‐STAT pathway (tofacitinib) are effective treatments for moderate to severe psoriasis patients. Still, current research on therapeutics for psoriasis is greatly facilitated by animal models developed to mimic human psoriasis disease . Although the field has advanced considerably, and the biologics changed the lives of many psoriasis patients, there is still an unmet need for newly developed drugs and identification of drug targets in the treatment of psoriasis.…”
Section: Psoriasis: From Disease Pathogenesis To Disease Hallmarks Mmentioning
confidence: 99%
“…Still, current research on therapeutics for psoriasis is greatly facilitated by animal models developed to mimic human psoriasis disease. [27][28][29] Although the field has advanced considerably, and the biologics changed the lives of many psoriasis patients, there is still an unmet need for newly developed drugs and identification of drug targets in the treatment of psoriasis. In-depth knowledge on the disease pathogenesis, in part facilitated by in vitro skin models, will facilitate future drug development studies.…”
Section: Immune Cells and Cytokinesmentioning
confidence: 99%